Desenvolvimento, implantação e avaliação de um programa de monitoramento de temperatura de termocicladores - Santos, Elisa Abreu (2019)
This study aimed to develop, implement and evaluate the effectiveness of a thermocycler temperature monitoring program in a molecular biology laboratory. It was necessary to adapt a thermocycler analyzer and create procedures to ensure the quality of the temperature measurement. The program was implemented in 11 laboratories of the Brazilian National Cancer Institute (INCA), in a total of 41 thermocyclers, of which 44% were unsuitable for use. The number of tests with a recommendation to be repeated was used as an indicator of program effectiveness. Two data samples obtained before md after the program’s implementation, with 102 and 141 tests from 2011 and 2013 respectively were evaluated. There was a reduction of 18.9 percentage points in the number of tests. In the interview with the staff, there were no change in the other determinants of the performance of the test t(9;22) BCR/ABL gene rearrangement in this period. The operational cost of repeating the test was estimated for the INCA laboratories and within the Unified Hea1th System (SUS). These findings have warned about the need for systematic verification of the temperature of thermocyclers, which is sometimes neglected due to the trust placed in the equipment.